A82: Lyme Arthritis: an Emerging Clinical Problem in Nova Scotia, Canada. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Glaude, Pier D.; Huber, Adam M.; Mailman, Timothy; Ramsey, Suzanne; Lang, Bianca; Stringer, Elizabeth
Abstract : Background/Purpose: Lyme disease (LD) is an emerging problem in the Canadian province of Nova Scotia with a sharp rise in reported cases over the past 2 years, including cases referred to the pediatric rheumatology clinic in Halifax, the sole pediatric rheumatology referral centre in the province. This increase is likely related to an increase in the number and size of endemic areas in the province; it is expected that cases will continue to rise. We sought to characterize the demographics, clinical presentation, treatment course and musculoskeletal outcome of children with LD in our clinic. Methods: Subjects with a diagnosis of LD since 2008 were identified in the pediatric rheumatology clinic database. The medical records of patients with LD were reviewed for demographic variables, referral patterns, clinical presentation, investigations, treatment course, and outcome. Results: Seventeen patients were identified; all patients were referred for evaluation of arthritis. 76% of patients presented in 2012 and 2013. Median age was 11.5 years (2.6–15.8), 16 were male. All lived in known endemic areas with Lunenburg county being most common (59%); 76% did not recall a tick bite. Subjects were referred by their family physician (7), emergency department (4), orthopedic surgery (4), and infectious diseases (2). The median number of physician visits for MSK symptoms prior to rheumatology consult was 2 (range 1 to >5). Only one patient was referred with a known diagnosis of LD; LD was suspected in 37.5% of the remaining cases based on referral information. Six patients had prior joint aspiration, 2 of whom were treated for septic arthritis. Pain and/or swelling were reported by all patients; in those with swelling 47% were persistent/53% episodic. The median number of joints involved was 1, with 94% having knee involvement. Patients reported MSK–symptoms for a median of 2 months (range 0.1–11) prior to referral to rheumatology. Four patients had a history of neurologic manifestations of LD prior to MSK presentation, none of which were recognized as LD. ECG was done in 13 cases and was normal. Three patients had a history of erythema migrans. 14/17 patients have completed antibiotic treatment. Arthritis resolved in 50% of patients after 1 course of antibiotics and 29% after 2 courses. A third course of antibiotics was required in 21% of patients for persistent arthritis. Two patients continued to have arthritis following completion of antibiotic therapy. At a median of 5 months (range 0–50) following treatment, there are 2 patients with persistent synovitis and functional limitations; one having evidence of joint damage despite extensive arthritis treatment (NSAID, steroid injection, DMARDs and a biologic). Conclusion: Increasing numbers of children with Lyme arthritis are being seen in the pediatric rheumatology clinic in Nova Scotia. LD was not considered as a diagnosis in the majority of cases by the referring physician. A quarter of patients also had a history of unrecognized neurologic manifestations of LD. In keeping with published North American reports, most patients had an excellent outcome however a proportion continued to have arthritis and disability following antibiotic therapy.